2017
DOI: 10.1136/neurintsurg-2017-013310
|View full text |Cite
|
Sign up to set email alerts
|

Physician training protocol within the WEB Intrasaccular Therapy (WEB-IT) study

Abstract: A new program of neurovascular-replicator-based physician training was employed within the WEB-IT study. This represents a new methodology for education and training that may be an effective means to optimize technical success and patient safety during the introduction of a new technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Therefore, the trial cases represent the first clinical experience that US physicians had with the device. A training program, which included hands-on experience using a lifelike simulator, was used 10. This program helped to familiarize investigators with the device’s characteristics, sizing, and deployment.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the trial cases represent the first clinical experience that US physicians had with the device. A training program, which included hands-on experience using a lifelike simulator, was used 10. This program helped to familiarize investigators with the device’s characteristics, sizing, and deployment.…”
Section: Methodsmentioning
confidence: 99%
“…10 Our fluoroscopy time of 34 minutes (AE18) is similar to other WEB related studies. 27,28 For all variables related to procedure times and radiation, the use of single implant solutions versus implantation of multiple devices carries an intuitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the benefit of using selected anatomies for evaluating device behavior and hands-on demonstration in artificial training settings 27. A study performed by Arthur et al in 2018, incorporated in the WEB Intrasaccular Therapy Study28 demonstrated the significance of creating a physical environment comprising a vascular simulator with patient-specific anatomies for education and training when introducing new technologies in clinical practice 27. HANNES may be particularly well qualified for such endeavors given its modular design, which allows easy testing of devices across a range of relevant anatomies.…”
Section: Discussionmentioning
confidence: 99%